Antimicrobial Resistance among Pregnant Women with Urinary Tract Infections Attending Antenatal Clinic at Levy Mwanawasa University Teaching Hospital (LMUTH), Lusaka, Zambia. (4th March 2021) - Yeta, Kekelwa Inyambo; Michelo, Charles; Jacobs, Choolwe
Abstract : Introduction . Globally, there is a growing concern over antimicrobial resistance (AMR) which is currently estimated to account for more than 700, 000 deaths per year worldwide. AMR undermines the management of infectious diseases in general especially in pregnancy where significant bacteriuria continues to be a serious cause of maternal and perinatal morbidity and mortality. We therefore aimed to determine the prevalence of AMR and the associated factors among pregnant women with urinary tract infections (UTIs) attending antenatal clinic at a selected hospital in Lusaka, Zambia. Methods . This was a hospital-based, cross-sectional study conducted between November 2018 and May 2019. Interviewer-administered questionnaire was used to assess the sociodemographic characteristics and behavioural characteristics. Laboratory tests were also conducted. Descriptive statistics of study participants were used to describe the characteristics of the respondents. Chi-square was used to assess the association between categorical variables. The logistic regression analysis was carried out to generate the adjusted odds ratio with 95% confidence interval. Results . Overall ( n = 203), the prevalence of UTI was 60% (95% CI: 53.3%–66.7%). The most isolated bacteria were E. coli (59%) and Klebsiella (21%). The prevalence of AMR was found to be 53% (95% CI: 46.1%–59.8%). The drugs highly resistant to antimicrobials were nalidixic acid (88.3%), ampicillin (77.8%), and norfloxacin (58.5%), while the least resistant drug was chloramphenicol (20%). There were no important significant predictors to AMR among pregnant women observed in this study. Conclusion . We found high burden of AMR closely linked to observe high prevalence of UTI suggested in this small population. This suggests a need to develop integrated surveillance systems that aim for early and regular screening of pregnant women for UTI as well as concurrent determination of antibiotic susceptibility patterns. This is important to prevent complications that may endanger maternal and fetal health outcomes. Furthermore, further research is needed to explore reasons for this high prevalence of AMR including examining possible attribution to the misuse of drugs so as to inform, enforce, or adjust the prescription-only policies and enforce antimicrobial stewardship programs.